Valores hematológicos de morcegos hematófagos Desmodus rotundus (E. Geoffroy, 1810) mantidos em cativeiro - Almeida, Breno F. M. de [UNESP]; Barbosa, Tatiana Sousa [UNESP]; Ciarlini, Luciana Del Rio Pinoti [UNESP]; Pedro, Wagner André [UNESP]; Belucio, Mário Luis [UNESP]; Queiroz, Luzia Helena [UNESP]; Ciarlini, Paulo César [UNESP] (My University, 2010)
Hematological values from captive vampire bats Desmodus rotundus (E. Geoffroy, 1810). Desmodus rotundus is one of the hematophagous bat species that are responsible for significant losses to livestock and has important involvement on public health. The great interest on this bat species made it becomes the target of many investigations a required its maintenance in laboratories. Similarly to others mammals, hematological evaluation has been utilized to assess the health and morbidity state of bats, however there are scarce studies with captive bats. The aim of this study was to investigate the hypothesis that is possible to feed the vampire bat D. rotundus with frozen blood treated with citrate during a long captivity period without hematological dyscrasias. Therefore, complete blood count was performed monthly from 15 adult females kept for 345 days in cages and fed with frozen blood added to citrate. The erythrocyte concentration (9.02 ± 1.43 x1012/L), PCV (0.47 ± 0.08 L/L) and hemoglobin (163.9 ± 31.5 g/L) obtained from free-living bats (immediately after capture) were lower or similar to those obtained after 345 days of captivity, presenting erythrocytes’ count of 11.01 ± 0.82 x1012/L, packed cell volume of 0.50 ± 0.05 L/L and hemoglobin level of 158 ± 10.1 g/L. The total white blood cell (11.09 ± 6.07 x109 /L) and segmented neutrophil counts (9.85 ± 3.5 x109 /L) of free living D. rotundus decreased significantly after 345 days of captivity, with values of 3.98 ± 1.98 and 1.87 ± 978.6 x109 /L respectively, which are similar to bats from temperate regions in hibernation period. This study proved that is possible to feed D. rotundus for long periods of captivity with citrated blood without the occurrence of anemia, erythrocyte or other hematologic dyscrasia

Desmodus rotundus é a espécie de quiróptero hematófago responsável por significativos prejuízos à pecuária e à saúde pública. O grande interesse sobre esta espécie tornou-a alvo de muitas investigações que exigem sua manutenção em laboratórios. Assim como em outros mamíferos, a avaliação hematológica tem sido utilizada para avaliar o estado de higidez e de morbidade dos quirópteros, porém são escassos os estudos com quirópteros mantidos em cativeiro. O presente estudo teve como objetivo investigar a hipótese de que é possível alimentar morcegos hematófagos D. rotundus com sangue citratado congelado por longo período em cativeiro sem que ocorra discrasias hematológicas. Para tal, realizou-se mensalmente o hemograma completo de 15 fêmeas adultas mantidas por 345 dias em gaiolas e alimentadas com sangue total citratado congelado. A concentração de eritrócitos (9,02 ± 1,43 x1012/L), volume globular (0,47 ± 0,08 L/L) e hemoglobina (163,9 ± 31,5 g/L) obtidos dos morcegos de vida livre (logo após a captura) foram menores ou similares aos dos obtidos após 345 de cativeiro, com valores de hemácias 11,01 ± 0,82 x1012/L, VG de 0,50 ± 0,05 L/L e hemoglobina de 158 ± 10,1 g/L. A contagem total de leucócitos (11,09 ± 6,07 x109 /L) e segmentados (9,85 ± 3,5 x109 /L) de D. rotundus de vida livre baixaram significativamente após 345 dias de cativeiro, chegando a valores de 3,98 ± 1,98 e 1,87 ± 978,6 x109 /L respectivamente, tornando-se semelhantes aos de morcegos de clima temperado sob hibernação. Foi comprovado que é possível manter o D. rotundus alimentados por longo período com sangue citratado sem que ocorra anemia, eritrócito ou qualquer outra discrasia hematológica.
Keywords: Chiroptera; Vampire bats; Reference values; Hematology; Quirópteros; Morcegos vampiros; Confinamento; Hemograma